Assessment of contamination of the Svitava and Svratka rivers in the Czech Republic using selected biochemical markers - Blahová, Jana; Havelková, Marcela; Kružíková, Kamila; Hilscherová, Klára; Halouzka, Roman; Modrá, Helena; Grabic, Roman; Halírová, Jarmila; Jurčíková, Jana; Ocelka, Tomáš; Haruštiaková, Danka; Svobodová, Zdeňka (Environmental toxicology and chemistry, 2010)
The aim of the present study is to assess aquatic ecosystem contamination using selected biochemical markers: cytochrome P450, ethoxyresorufin-O-deethylase (EROD), glutathione S-transferase (GST), tripeptide glutathione, vitellogenin, and 11-ketotestosterone in chub (Leuciscus cephalus L.). Seven locations on the Svitava and Svratka rivers (in the Brno conurbation, Czech Republic) were assessed. The results were compared with the levels of the most important inductors of these biomarkers: organic pollutants hexachlorocyclohexane (HCH), hexachlorobenzene (HCB), DDT and its metabolites, polychlorinated biphenyls, and polycyclic aromatic hydrocarbons in bottom sediment, fish muscle, and semipermeable membrane devices (SPMDs) and metals in sediment. The highest levels of pollutants were observed at sites situated downstream from Brno, especially at Modrice and Rajhradice. Significant positive correlations (p < 0.05) were found between EROD activity and HCH concentration in SPMDs, and also between GST and EROD activity with HCB concentration in muscle, after adjusting for age.
Keywords: Environmental Monitoring; Glutathione Transferase; Water Pollutants, Chemical; Endocrine Disruptors; zvířata; Czech Republic; cytochrom P-450 CYP1A1; testosteron; řeky; mužské pohlaví; Česká republika; Cytochrome P-450 CYP1A1; Rivers; vitelogeniny; Vitellogenins; biologické markery; Organic Chemicals; Testosterone; Animals; organické látky; chemické látky znečišťující vodu; Biomarkers; Cyprinidae; Male; monitorování životního prostředí; endokrinní disruptory; glutathiontransferasa